The effect of moderate and high-intensity fatigue on groundstroke accuracy on expert and non-expert tennis players - Lyons, M.; Al-Nakeeb, Y.; Hankey, J.; Nevill, A. (Journal of Sports Science & Medicine, 2013)
Exploring the effects of fatigue on skilled performance in tennis presents a significant challenge to the researcher with respect to ecological validity. This study examined the effects of moderate and high-intensity fatigue on groundstroke accuracy in expert and non-expert tennis players. The research also explored whether the effects of fatigue are the same regardless of gender and player's achievement motivation characteristics. 13 expert (7 male, 6 female) and 17 non-expert (13 male, 4 female) tennis players participated in the study. Groundstroke accuracy was assessed using the modified Loughborough Tennis Skills Test. Fatigue was induced using the Loughborough Intermittent Tennis Test with moderate (70%) and high-intensities (90%) set as a percentage of peak heart rate (attained during a tennis-specific maximal hitting sprint test). Ratings of perceived exertion were used as an adjunct to the monitoring of heart rate. Achievement goal indicators for each player were assessed using the 2 x 2 Achievement Goals Questionnaire for Sport in an effort to examine if this personality characteristic provides insight into how players perform under moderate and high-intensity fatigue conditions. A series of mixed ANOVA's revealed significant fatigue effects on groundstroke accuracy regardless of expertise. The expert players however, maintained better groundstroke accuracy across all conditions compared to the novice players. Nevertheless, in both groups, performance following high-intensity fatigue deteriorated compared to performance at rest and performance while moderately fatigued. Groundstroke accuracy under moderate levels of fatigue was equivalent to that at rest. Fatigue effects were also similar regardless of gender. No fatigue by expertise, or fatigue by gender interactions were found. Fatigue effects were also equivalent regardless of player's achievement goal indicators. Future research is required to explore the effects of fatigue on performance in tennis using ecologically valid designs that mimic more closely the demands of match play.